Determination of Rotational Parameters of CH3CN, CD3CN and their Different Isotopic Species in the Ground and v4 = 1 States - Masoud Motamedi; Parinaz Moradi (E-Journal of Chemistry)
The millimeter-wave rotational spectra of the symmetric top molecules CH3CN, 13CH3CN, CH313CN, CH3C15N, CD3CN , 13CD3CN, CD313CN and CD3C15N have been investigated again in their ground and v4 = 1 states. The analysis of spectra and fitting the frequencies in these states give rotational parameters with higher accuracy compare with previous works. The parameter HJ = -0.107(96) mHz was determined for CH3C15N for the first time.